Corruption as discourse of dis-enfrenchisement - Green, Florence F.; Siziba, Nicholas N. (IOSR Journal Of Humanities And Social Science, 2017)
This paper looks at corruption as a diversionary, amorphous and neo-colonial idea used by the West to denigrate African leaders and their achievements after uhuru. "Diversionary" because the term is used as a decoy to mislead African peoples and their leaders. Instead of striving for material democracy and well-being, the Africans are set on an anti-corruption crusade, pursuing mirages of transparency, accountability, good democratic governance as defined for all by the same West. "Good and free" Africans are expected to be seen and heard chasing or challenging their leaders into joining the anti-corruption crusade. The term corruption became fashionable with the decolonization of Africa in the 1960s and thus became synonymous with postindependence African leaders and governments. The term is amorphous in that it has no definite meaning and has different meanings to different people.